Therapeutic Alliance and Outcome of Psychotherapy: Historical Excursus, Measurements, and Prospects for Research - Ardito, Rita B.; Rabellino, Daniela (Frontiers in Psychology, 2011)
This paper proposes a historical excursus of studies that have investigated the therapeutic alliance and the relationship between this dimension and outcome in psychotherapy. A summary of how the concept of alliance has evolved over time and the more popular alliance measures used in literature to assess the level of alliance are presented. The proposal of a therapeutic alliance characterised by a variable pattern over the course of treatment is also examined. The emerging picture suggests that the quality of the client–therapist alliance is a reliable predictor of positive clinical outcome independent of the variety of psychotherapy approaches and outcome measures. In our opinion, with regard to the relationship between the therapeutic alliance and outcome of psychotherapy, future research should pay special attention to the comparison between patients’ and therapists’ assessments of the therapeutic alliance. This topic, along with a detailed examination of the relationship between the psychological disorder being treated and the therapeutic alliance, will be the subject of future research projects.